Criminological Aspects on Gender-Based Exploitation: The Existence of Female Objectification in Online Gambling Promotions - Julianti, Shinta; Nurhadiyanto, Lucky Nurhadiyanto; Gustiman, Jepri; Nurrahma Masturi, Frida; Rostikawati, Rin (PAMPAS: Journal of Criminal Law, 2025)
This research analyzes from a criminological perspective the issue of gender-based exploitation, specifically the role of the objectification of women in promoting online gambling to achieve the existence of online gambling. The research method used is descriptive qualitative, with data collection techniques through literature study, observation, and interviews. This research also employs a legislative and sociological approach. The results of the research found that online gambling promotion systematically uses narratives and visuals that reduce women to sexual attractions or means to achieve false pleasure. This objectification is carried out through vulgar advertisements, representing the female body that attracts sexual desire. From a criminological perspective, this practice is a form of gender-based exploitation because it exploits the social and economic vulnerabilities of women, reinforces negative stereotypes, and indirectly contributes to the normalization of symbolic violence. From the perspective of positive law, the act violates several regulations, including the Anti-Trafficking in Persons Act, CEDAW, the Electronic Information and Transactions Law, the Pornography Law, and the Sexual Violence Crime Law. Abstrak Penelitian ini menganalisis secara kriminologis terkait eksploitasi berbasis gender, khususnya peran objektifikasi perempuan dalam promosi perjudian online untuk mencapai eksistensi. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui studi pustaka, observasi dan wawancara. Penelitian ini juga menggunakan pendekatan terhadap peraturan perundang-undangan dan pendekatan sosiologis.  Hasil dari penelitian ditemukan bahwa promosi perjudian online secara sistematis menggunakan narasi dan visual yang mereduksi perempuan sebagai simbol daya tarik seksual menjadi sarana untuk mencapai kesenangan semu. Objektifikasi ini dilakukan melalui iklan yang vulgar, merepresentasi kebertubuhan perempuan yang menarik hasrat seksualitas. Secara kriminologis, praktik ini merupakan bentuk eksploitasi berbasis gender karena memanfaatkan kerentanan sosial dan ekonomi perempuan, memperkuat stereotip negatif, dan secara tidak langsung berkontribusi pada normalisasi kekerasan simbolik. Dalam perspektif hukum positif, perbuatan tersebut melanggar sejumlah regulasi diantaranya UU TPPO, CEDAW, UU ITE, UU Pornografi dan UU TPKS.